Suangi dalam Perspektif Masyarakat Beragama Kristen di Pulau Semau - Ferdilianto Sandelgus, Rolin; Haan, Arly Elizabeth Maria de (Danum Pambelum: Jurnal Teologi dan Musik Gereja, 2025)
Until now, beliefs about magical things are still believed by modern society. One of them is seen through the life of the Semau community. In this area, people still believe in the existence of spirits. Belief in the existence of these spirits is also often used to do many things, such as for traditional medicine but can also be used to harm others. The reality of this magical element is known as Suanggi. In fact, according to the data, almost all Semau people identify themselves as religious people. Of course, this reality is also a challenge in itself, for religions, especially Christianity, in making a balanced distinction between which cultures have a good impact on human life and which ones harm humans. The church must of course be selective in theologizing culture. Therefore, through this writing, it is hoped that it can provide a contribution of thought for churches in NTT, especially GMIT in theologizing with culture. In order to complete this paper, the author uses an interdisciplinary approach that does provide space for dialogue for many related scientific groups, which can conflict with each other but also work in harmony.